Six-Digit CPK and Mildly Affected Renal Function in McArdle Disease - George Spyropoulos; Panagiotis Kratimenos; Andrew D. Mcinnes; Richard J. DeGroote; Ioannis Koutroulis (Case Reports in Pediatrics)
A previously healthy, white 12-year-old girl presented with diffuse body aches and poor perfusion. She developed severe respiratory failure and marked rhabdomyolysis and was mechanically ventilated. Although her CPK peaked at 500,000 IU/L, her renal function was mildly affected and her creatinine did not exceed the 0.8 mg/dL. The rhabdomyolysis was gradually resolved following aggressive fluid hydration. The patient did not require dialysis and made a complete recovery. Genetic studies revealed the diagnosis of McArdle disease.